Mid- to late-Holocene paleoenvironmental changes inferred from organic geochemical proxies in Lake Tangra Yumco, Central Tibetan Plateau. (October 2017) - Wang, Yong; Wang, Junbo; Zhu, Liping; Lin, Xiao; Hu, Jianfang; Ma, Qingfeng; Ju, Jianting; Peng, Ping; Yang, Ruimin
Investigations of the paleoclimate and paleoenvironmental changes in the Tibetan Plateau in recent years have led to many significant achievements. However, high-resolution lake records from the mid- to late-Holocene have not been determined for the Central Tibetan Plateau, which is in the transition zone between the Indian summer monsoon (ISM) system and the westerlies. In this study, we analyzed the distribution and compound-specific carbon isotope compositions ( δ 13 C) of sedimentary n -alkanes and the bulk sediment total organic matter (TOC), total nitrogen (TN), and C/N ratios to reconstruct the paleoenvironmental changes over the past 6 cal. ka BP using a 376-cm sediment core from the southern basin of Tangra Yumco, Central Tibetan Plateau. Our results indicated that clear stepwise decreases in lake productivity and lake level occurred during the mid- to late-Holocene based on decreases in δ 13 C values of mid-chain n -alkanes and P aq (an n -alkane-based proxy). Additionally, the variations in the TOC, TN, and C/N ratios revealed generally increased inputs of allochthonous organic matter over the past 6 cal. ka BP. When our findings at Tangra Yumco were compared with records from the Central Tibetan Plateau and adjacent regions, we found generally consistent patterns of lake environmental changes over the past 6 cal. ka BP, suggesting that the climate of the Central Tibetan Plateau was primarily influenced by the ISM system at the millennial time scale. Therefore, our results depict the evolution of the ISM over the past 6 cal. ka BP in the Central Tibetan Plateau, which corresponds to summer solar insolation and the migrations of the Intertropical Convergence Zone (ITCZ). We also propose that the climate of the North Atlantics influenced the climate of the Central Tibetan Plateau through some indirect climatic mechanisms.